Mars adapting : military change during war - Hoffman, Frank G. (Transforming war., 2021)
"Future naval leaders need to embrace continuous assessment during wartime and create the conditions in order to support organizational learning and the need to adapt. Wars are usually won by the best learners and adapters, not the military with the best technology or best forecasted pre-war doctrine. To be able to learn quickly, leaders at all levels must be open to new conceptions of tactics and technologies and avoid locking into mentalities from prior experiences that block adaptation"--